Prevalencia de hematuria enzoótica en bovinos del cantón Balsas mediante tiras reactivas - Rojas Atience, Danilo Aurelio (2013)
This research was conducted in the canton Balsas, from March 7, 2013 until May 18, 2013, in order to determine by the method of test strips (urinalysis) the presence of vesical hematuria bovine enzootic in existing in that district. For the present investigation the following aims: 1. Determine the prevalence of Bovine Enzootic Hematuria Bladder by dipstick Balsas Canton herds. 2. Determine the prevalence of Bovine Enzootic Hematuria Bladder according to race, sex and age of the animals sampled. While researching this work, urinalysis to 600 cattle of all ages in the different herds of Canton, for a period of 73 days. Animals that were investigated Bellamaría came from the parish, and all sites belonging to the canton Balsas. The results determined that if there is the presence of enzootic Hematuria in cattle Bladder existing in that district.